Hypothesis-based interventions for tantrum behaviors of persons with developmental disabilities in school settings. - Repp, A C (1994)
We conducted a functional assessment of problem behaviors of 2 students with developmental disabilities in their classroom environments. Results of the assessments showed that although there were more tantrums in demand than in no-demand conditions, the function of the behavior was to gain attention (positive reinforcement) rather than to avoid or escape demands (negative reinforcement); demand conditions apparently served a discriminative function for the availability of attention. Therefore, intervention was based on the positive reinforcement hypothesis, resulting in a substantial reduction of tantrums for both subjects.